VARIASI INDIVIDUAL PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: KAJIAN TENTANG INTELEGENSI, GAYA BELAJAR, GAYA BERPIKIR, KEPRIBADIAN, DAN TEMPERAMEN - Muhammad Rivaldi Rivaldi; Rohana Rohana; Muh.Andri Muh.Andri; Depri Depri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Every learner is a unique individual with distinct characteristics, so the success of Islamic Religious Education (PAI) learning is determined not only by the curriculum, materials, and methods, but also by the individual variations inherent in each learner. This article aims to examine learners' individual variation in PAI learning, covering five main aspects: intelligence, learning style, thinking style, personality, and temperament. This study employs a library research method, reviewing books, scholarly journals, and relevant Qur'anic verses and hadith, which are then analyzed descriptively and qualitatively. The findings show that intelligence affects the speed and depth of learners' understanding of textual and rational religious evidence; visual, auditory, and kinesthetic learning styles determine how learners absorb religious material; impulsive-reflective and deep-surface thinking styles influence the depth of value internalization; while personality and temperament shape learners' religious attitudes and behavior. Islam views individual variation as part of human nature (fitrah) and divine law (sunnatullah) that must be treated justly through the principle of obligation according to capacity (QS. Al-Baqarah: 286). This study recommends that PAI teachers implement differentiated learning, diagnostic assessment, and varied learning strategies and media so that every learner can develop optimally in cognitive, affective, and psychomotor aspects, toward the formation of knowledgeable and morally excellent individuals.